Comparison of Lipid Profile in Different Types of Steroid Sensitive Idiopathic Relapsing Nephrotic Syndrome in Children during Active Disease and Remission (Medicine Today, 2022)
Introduction: Nephrotic syndrome is a disease of relapse and remission. Relapse rate is more than 80%. Hyperlipidemia and hypoalbuminemia are important characteristic of nephrotic syndrome. Hyperlipidemia persist even after remission of disease in frequent relapse nephrotic syndrome possibly due to frequent attack of disease and frequent use of steroid. Hyperlipidemia causes premature atherosclerosis, progressive renal injury leading to chronic renal failure, cardiac complications (myocardial infarction, hypertension), cerebrovascular disease and frequent relapse of nephrotic syndrome.Objectives: The aim of study was to see the lipid profile and comparison of lipid profile among different types of steroid sensitive idiopathic relapsing nephrotic syndrome during active disease and in remission.Materials and Methods: A cross sectional study included 120 ( 40 in each group) children aged 2-16 years with steroid sensitive idiopathic relapsing nephrotic syndrome patients who were admitted or attended in out patients department (OPD) in paediatric nephrology department Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, during December 2014 to December 2015. They were clinically examined and fasting lipid profile was done in each case during active disease and after one month of urinary remission. The study population were divided into three groups- Infrequent relapse nephrotic syndrome (IFRNS), frequent relapse nephrotic syndrome ( FRNS ) and steroid dependent nephrotic syndrome (SDNS) based on clinical response.Results: Total patients were 120 (40 in each group). The study showed a male predominance with a male to female ratio 2.24:1, male patients were 69%, female 31%. In all cases, there were increased mean total cholesterol, low density lipoprotein ( LDL ) , triglyceride (TG) and high density lipoprotein (HDL) was normal during active disease, more raised in FRNS and SDNS.There was significant decrease in the mean level of total cholesterol, LDL and triglyceride during remission ( p